2019
DOI: 10.5812/ijcm.69683
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Clinical Assessment, Mammography, and Ultrasonography in Diagnosis of Benign and Malignant Breast Lesions and Determining Their Cost-Effectiveness

Abstract: Background:In order to evaluate the diagnostic capabilities of various methods of breast cancer, it was expected that the use of non-invasive imaging techniques would be the earliest and the best technique of patient management. Objectives: We attempted to evaluate mammography and ultrasonography reports along with clinical diagnosis and their agreement with the definite diagnosis of breast lesions by pathology report. Methods: This cross sectional study was conducted on 287 women, who were referred to the can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Akbari et al (31) reported that more than 50% of the diagnostic imaging in primary breast cancer diagnosis are not matched with pathologic report as the golden standard of cancer diagnosis due to lack of spending time by radiologists and quality of their equipment.…”
Section: Discussion About Resultsmentioning
confidence: 99%
“…Akbari et al (31) reported that more than 50% of the diagnostic imaging in primary breast cancer diagnosis are not matched with pathologic report as the golden standard of cancer diagnosis due to lack of spending time by radiologists and quality of their equipment.…”
Section: Discussion About Resultsmentioning
confidence: 99%